DEFINING THE CONCEPT OF ARTS AND CULTURE IN HIGHER EDUCATION SYSTEMS IN INDONESIA - Pham Tran Minh Thi (Imaji, 2020)
An understanding of art and culture has often been known by many Indonesian students and also the community. These two words are always a pair of words in the vocabulary of the Language and Arts department in particular. there is art where the culture is, and vice versa culture is never released by the art. However, the definitions of "culture" and "art" require attention to be redefined towards supporting the new mental revolution held by the Indonesian government, and also to follow the world's advanced higher education system. In our opinion, it is better for the field of "culture" and the field of "art" to be understood as both becoming two scientific fields themselves. Then, understanding the arts in its position in relation to the cultural field from its elements related to awakening the cultural field occurs the need to develop a good arts education curriculum. Finally, Vietnamese character education is explained via the concept of mind relating to its culture and the characteristics of their nation. these problems will be discussed in this paper. Keywords: art, culture, mental revolution, art education